2020
DOI: 10.1097/hcr.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Behavioral Weight Loss and Weight Loss Goal Setting in Cardiac Rehabilitation

Abstract: Purpose-Obesity is prevalent among participants in cardiac rehabilitation (CR). Establishing a weight loss goal is an important strategy for promoting weight loss. We evaluate the association between a pre-program weight loss goal and change in weight during CR.Methods-Body weight was measured at CR entry and at exit from CR. Overweight/obese participants were categorized as having: (1) established a weight loss goal and attended behavioral weight loss sessions (G+ BWL); set a weight loss goal but did not atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…27 In another retrospective study, patients who set a weight loss goal and attended behavioral weight loss sessions lost significantly more weight than those who did not participate in any weight management activities (−6.8% vs +1.6%). 28 Although goal setting alone was better than nothing at all, session attendance was the strongest predictor of weight loss. Similarly, participation in Weight Watchers for 10-14 wk resulted in an average weight loss of 5.6%, with more than half reducing their body weight by ≥5%.…”
Section: Discussionmentioning
confidence: 98%
“…27 In another retrospective study, patients who set a weight loss goal and attended behavioral weight loss sessions lost significantly more weight than those who did not participate in any weight management activities (−6.8% vs +1.6%). 28 Although goal setting alone was better than nothing at all, session attendance was the strongest predictor of weight loss. Similarly, participation in Weight Watchers for 10-14 wk resulted in an average weight loss of 5.6%, with more than half reducing their body weight by ≥5%.…”
Section: Discussionmentioning
confidence: 98%
“…However, unlike lifestyle behaviors such as physical activity, weight loss is not a behavior but a potential outcome from changes in lifestyle behaviors. It is suggested that larger weight‐loss goals may be associated with greater subsequent weight loss with lifestyle intervention [25]. More than 95% of our patient population had weight‐loss goals of greater than the 5% to 10% weight loss, which is commonly recommended for health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that patients in CR who set a weight loss goal are more likely to accomplish weight loss than patients who do not. 54,55 Thus, a part of the initial case manager evaluation should include setting a realistic weight loss goal in CR. 54,55 PRACTICAL CONSIDERATIONS Every CR program needs to lay out a practical, workable approach to weight reduction, given its resources, staffing, and patient population.…”
Section: Strength Of Evidence Amentioning
confidence: 99%
“…54,55 Thus, a part of the initial case manager evaluation should include setting a realistic weight loss goal in CR. 54,55 PRACTICAL CONSIDERATIONS Every CR program needs to lay out a practical, workable approach to weight reduction, given its resources, staffing, and patient population. Ignoring obesity in cardiac patients is not an option.…”
Section: Strength Of Evidence Amentioning
confidence: 99%